Preliminary study on serum immunoglobulin G responses following intramuscular inoculation of adjuvanted polyhydroxyalkanoate microparticles with Pasteurella multocida vaccine in white rats. (June 2021) - Mohamed, Shazwani; May Amelia, Tan Suet; Abdullah Amirul, Al-Ashraf; Abdul Wahid, Mohd Effendy; Bhubalan, Kesaven
Abstract: A natural biodegradable polymer, polyhydroxyalkanoate (PHA), was adjuvanted with a vaccine seed to observe the biomaterial's ability in enhancing an immune response in rats. The adjuvant potential of PHA was tested using the whole-killed Pasteurella multocida B:2 (PMB2) vaccine in Sprague Dawley (SD) rats to detect changes in serum immunoglobulin G (IgG) and immunoglobulin M (IgM) responses. A common PHA, poly(3-hydroxybutyrate) [P(3HB)], from Bacillus megaterium UMTKB-1 was constructed into microparticles using the solvent evaporation method. Twelve SD rats were divided into four treatment groups: 1) non-treatment as negative control, 2) P(3HB) adjuvant, 3) PMB2 vaccine, and 4) adjuvanted-P(3HB)/PMB2 vaccine groups, which were intramuscularly vaccinated twice. Immunoglobulins IgG and IgM levels were used as markers of the immune response induced by the adjuvanted-P(3HB)/PMB2 vaccine and analysed over an eight-week study period. The group vaccinated specifically with adjuvanted-P(3HB)/PMB2 vaccine had higher concentrations of immunoglobulins compared to other treatment groups, hence demonstrating the potential of the adjuvant to enhance immune response. Findings showed a need to delay the delivery of the second booster dose to determine the appropriate regime for the adjuvanted-P(3HB)/PMB2 vaccine.